Variable rate fertilizer application technology for nutrient management: A review - Pawase, Pranav Pramod; Nalawade, Sachin Madhukar; Bhanage, Girishkumar Balasaheb; Walunj, Avdhoot Ashok; Kadam, Pravin Bhaskar; Durgude, Anil G; Patil, Mahesh G (International Journal of Agricultural and Biological Engineering, 2023)
The efficient and effective application of fertilizers to crops is a major challenge. Conventionally, constant rate or equal dose of fertilizer is applied to each plant. Constant rate fertilizer application across entire field can result in over or under incorporation of nutrients. Fertilizer application is influenced by soil parameters as well as geographical variation in the field. The nutrient management depends on selection of nutrient, application rate and placement of nutrient at the optimal distance from the crop and soil depth. Variable rate technology (VRT) is an input application technology that allows for the application of inputs at a certain rate, time, and place based on soil properties and spatial variation in the field or plants. There are two approaches for implementing VRT, one is sensor based and another is map based. The sensor based approach; with suitable sensors, measures the soil and crop characteristics on-the-go calculating the amount of nutrients required per unit area/plant and micro controlling unit which uses suitable algorithms for controlling the flow of fertilizer with required amount of nutrient. In map based approach; Grid sampling and soil analysis are used to create a prescription map. According to the soil and crop conditions, the microcontroller regulates the desired application rate. The sensor-based VRT system includes a fertilizer tank, sensors, GPS, microcontroller, actuators, and other components, whereas the map-based system does not require an on-the-go sensor. Both approaches of VRT for fertilizer application in orchards and field crops are reviewed in this paper. The use of this advance technology surely increases the fertilizer use efficiency; improve crop yield and profitability with reduced environment impacts. Keywords: nutrient sensor, prescription map, spatial variation, VRTDOI: 10.25165/j.ijabe.20231604.7671Citation: Pawase P P, Nalawade S M, Bhanage G B, Walunj A A, Kadam P B, Durgude A G, Patil M R. Variable rate fertilizer application technology for nutrient management: A review. Int J Agric & Biol Eng, 2023; 16(4): 11-19.